2021
DOI: 10.1108/bij-09-2020-0470
|View full text |Cite
|
Sign up to set email alerts
|

An integrated framework for analysing performance indicators of Indian microfinance institutions: a multi-stakeholder perspective

Abstract: PurposeAn amalgamation of Decision-Making Trial and Evaluation Laboratory (DEMATEL) and Analytical Network Process (ANP) has been performed to develop a decision-making framework for improving the overall performance of the microfinance institutions. A primary survey was conducted to collect real-time data from the heterogeneous stakeholders of microfinance institutions across India. The validation of the proposed framework is performed by comparing the results against the conventional method of Analytical Hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Foerstl et al (2017) argued that the widespread of quality suppliers across the globe have expanded the supplier selection process. Studies by Masi et al (2013), van der Westhuizen and Ntshingila (2020) and Bardhan et al (2021) concluded that supplier selection is synonymous with improved business performance in both financial and non-financial dimensions. Arguably, exposure to supplier selection risks such as capacity risks, quality risks, quantity and communication risks could expose firms to quality issues and increased financial burden; in turn threatening the overall firm performance and competitiveness levels.…”
Section: Procurement Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Foerstl et al (2017) argued that the widespread of quality suppliers across the globe have expanded the supplier selection process. Studies by Masi et al (2013), van der Westhuizen and Ntshingila (2020) and Bardhan et al (2021) concluded that supplier selection is synonymous with improved business performance in both financial and non-financial dimensions. Arguably, exposure to supplier selection risks such as capacity risks, quality risks, quantity and communication risks could expose firms to quality issues and increased financial burden; in turn threatening the overall firm performance and competitiveness levels.…”
Section: Procurement Performancementioning
confidence: 99%
“…According to Malviya and Kant (2019), measuring procurement performance plays a significant role in predicting the performance of manufacturing firms and their supply chains. In fact, procurement performance measures the degree to which a procurement function or process meets expected goals at the most competitive costs (Jones and Kaluarachchi, 2008;Malviya and Kant, 2019;Tripathi and Gupta, 2019;Machado et al, 2019;Bardhan et al, 2021). Since risks account for more than 40% of firm performance (Nyamah et al, 2017); it would be prudent to investigate the risks residing in the various stages of manufacturing firms' procurement processes and their effects on procurement performance in the manufacturing sector in the West African region.…”
Section: Introductionmentioning
confidence: 99%
“…Another multi-criteria method for performance analysis has been proposed based on goal programming (Cervelló-Royo et al, 2019) considering social performance besides outreach and financial performance. Considering social and financial performance along with governance, Bardhan et al (2021) found interrelationship among these three factors in determining overall performance of MFIs. Ghose et al (2018) compared financial and social performance of MFIs based on their legal status and found that NGO-MFIs performs financially better as compared to NBFCs but there is no distinction among these two types of MFIs in terms of social performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The DEMATEL framework is a widely used and accepted multi-criteria decision-making (MCDM) model to establish dyadic relationships between decision-making factors in complex situations (Tarei et al , 2018). The framework has found several applications in different domains of management decision-making, namely, waste management (Singh and Sushil, 2021), risk management (Ramesh et al , 2020), supply chain (Tarei et al , 2018), microfinance (Bardhan et al , 2021), sustainability (Chand and Tarei, 2021) and Industry 4.0 (Nimawat and Gidwani, 2021; Tripathi, and Gupta, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%